2009
DOI: 10.1080/00032710903060735
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Application of New Resin Functionalized by Brilliant Green for Spectrophotometric Determination of Mercury in Environmental Samples

Abstract: A new chelating resin was prepared by coupling Amberlite XAD-4 with brilliant green through an azo spacer, and it has been used for preconcentration and separation of mercury(II) in environmental samples prior to its determination by spectrophotometry. The sorption capacity of functionalized resin is 4.12 mg g À1 . Spectrophotometric determination of Hg(II), free from the interference of almost all cations and anions found in the environmental water samples, is a notable advantage of the method. The determinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Several analytical methods have been applied for the determination of mercury in biological and environmental samples, such as spectrophotometry [13,14], atomic absorption spectrometry [15,16], stripping voltammetry [17][18][19][20] using a different electrodes as gold, glassy carbon, nanoparticles, and carbon paste electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Several analytical methods have been applied for the determination of mercury in biological and environmental samples, such as spectrophotometry [13,14], atomic absorption spectrometry [15,16], stripping voltammetry [17][18][19][20] using a different electrodes as gold, glassy carbon, nanoparticles, and carbon paste electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Preconcentration steps are commonly necessary to attain the levels required for reliable detection (Tarley, Dos Santos, et al 2004;. Several preconcentration procedures such as liquid-liquid extraction (Anthemidis et al 2004), micelle-mediated extraction (Chen and Teo 2001), co-precipitation (Tuzen and Soylak 2009), cloud point extraction (Candir, Narin, and Soylak 2008), and electrochemical methods (Kokkinos et al 2009) were reported in the literature, but solid-phase extraction (Ahmad FeizBakhsh et al 2009;Hashemi-Moghaddam, Ahmad Panahi, and Nikpour Nezhati 2009), mainly associated with flow injection analysis, is most frequently employed due to its advantages in terms of flexibility, simplicity, high-enrichment factor, easy regeneration of solid-phase, low reagent/sample consumption, and high sampling rate .…”
Section: Homayon Ahmad Panahi a Mahshid Nikpour Nezhati A Rohollahmentioning
confidence: 99%
“…Because of the disadvantages such as the interferences from matrix components, the necessity of operational expertise, and relatively higher costs of other methods [9,10], the use of preconcentration techniques in the determination of Co by flame atomic absorption spectrometry (FAAS) can still be of importance. Among preconcentration techniques, solid-phase extraction (SPE) is widely used due to its simplicity, high concentration factor, and more environmentally friendly reagents used [11,12].…”
Section: Introductionmentioning
confidence: 99%